The Critical Role of Psychological Capital in Empowering Female Managers Amid Digital Innovation - Widiati, Restu; Soetjipto, Budi W.; Siscawati, Mia; Jayanagara, Oscar (Pandawan, 2024)
Despite significant progress in gender equality, women continue to face underrepresentation in leadership roles, with many opting out of corporate careers due to persistent barriers. This is concerning, as the career advancement of women depends on their ability to stay engaged and perform effectively in the workplace which continues to adopt digital innovations. The study examines the critical role of Psychological Capital (PsyCap) in empowering female managers, especially as organizations continue to embrace digital innovations. The study also explores how Leader-Member Exchange (LMX) strengthens this relationship, contributing to performance and engagement in the workplace. This study was conducted in two subsidiaries of a multinational company, in India and Indonesia. We applied a mixed method with quantitative analysis from 104 completed questionnaires, and qualitative analysis from interviewing a total of 13 participants from both countries. The quantitative analysis shows that PsyCap plays a significant role in enhancing LMX, fostering DIB, and improving both performance and engagement. Qualitative findings highlight three core themes that emphasize how PsyCap supports female managers in navigating digital transformation challenges. This study examines PsyCap within the framework of LMX and DIB, highlighting the pivotal role of PsyCap and its dynamic interactions in enhancing the performance and engagement of female managers. Conducted in India and Indonesia, this study offers a unique cross-cultural perspective on the role of PsyCap in empowering female managers amidst digital innovation, addressing gaps in existing literature by focusing on South Asian contexts with low gender equality rankings.